MANAJEMEN MODAL KERJA DAN PROFITABILITAS PERUSAHAAN PADA SIKLUS BISNIS YANG BERBEDA (Studi kasus perusahaan yang tercatat dalam Bursa Efek Indonesia periode 2007-2010) - Dewi, Febrina Eka; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2018)
The recent economic downturn of 2008â€“2009 has brought renewed focus on working capital policies in Indonesia. The crimping consumer demand in economic downturn rapidly exhausts the working capital of businesses. Economic policy aimed at boosting cash flows of firms, either directly or indirectly, can be of enormous benefit in alleviating pressure on working capital.Â The purpose of this research is to analyze the relationship between working capital management and profitability in different business cycle. The population of this research is all of the firms listed on Indonesia Stock Exchange in period of 2007-2010. The samples were selected by purposive sampling method and do outlier to remain 39 companies. Method used in this research is Ordinary Least Square (OLS) with SPSS 23.0 as the analysis instrument.Â The result of this research shows cash conversion cycle and inventory conversion period have a negative and significant effect. But receivable collection period and payable deferral period have insignificant effect on the firm's profitability. During crisis period, only cash conversion cycle indicate a negative and significant relation with firm profitability. During economic boom, receivable collection period has a negative and significant relation to profitability. Inventory conversion period has a positive and significant relation during economic boom.